2004
DOI: 10.1002/maco.200303775
|View full text |Cite
|
Sign up to set email alerts
|

Metallic dental materials in patient's oral cavity acting as electrodes of electrochemical cells

Abstract: The work was aimed at studying of standard potentials of commonly used metallic dental materials and determining of the effect of saliva conductivity and reaction on value of the potentials. The following materials have been examined: gold alloy (a material used for crowns and bridgeworks), chromium-cobalt alloy (for frameworks in removable partial dentures), and silver amalgams (used for fillings) manufactured by three different companies.Taking into account that mucosa makes one of the electrodes existing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, it is worth noting that a recent study has shown that metallic dental materials can produce significant EMFs as they form galvanic cells with the mucosa or other dental implants. It is possible that such EMFs could combine with the induced current in such a way as to reduce the threshold for sensing a metallic taste (11). It is also reasonable to assume that the conductive pathways around the oral cavity and across the tongue will be modified by the presence of metal fillings.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that a recent study has shown that metallic dental materials can produce significant EMFs as they form galvanic cells with the mucosa or other dental implants. It is possible that such EMFs could combine with the induced current in such a way as to reduce the threshold for sensing a metallic taste (11). It is also reasonable to assume that the conductive pathways around the oral cavity and across the tongue will be modified by the presence of metal fillings.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may complain of a "metallic taste" sensation when they move near the MRI scanner; this electrogustatory effect depends on the motion rate and direction with respect to the MRI magnetic field. Although the source of this phenomenon is not generally agreed upon (75), some have proposed that it could be related to the electrolysis of metallic dental fillings during translation through the SFG (63,76). Cavin et al (75) found that 12 of 21 subjects experienced metallic taste sensations when moving their heads in 7-T fields just outside the T but not at 1.5 T (86); further studies validating this finding and determining how it may impact human subjects are warranted.…”
Section: Tonguementioning
confidence: 99%
“…However, because the nerve density in the different esophageal layers is unknown, we can only predict an association between the stimulation volume and the subjective pain score. Impedance in the human esophagus can vary due to different local conditions in the esophageal mucosa and saliva production [ 25 ], but also food or refluxed gastroduodenal content [ 26 ] can explain that we measured higher impedance in vivo than in the simulations. However, a difference in this parameter may also occur due to limitations of isotropic models.…”
Section: The Electrical Stimulusmentioning
confidence: 99%